Prevalence of abnormal serum cholinesterase among the vegetable farmers in a district - Boonkhao, Laksanee; Baukeaw, Warisin (Health Science, Science and Technology Reviews, 2020)
This study aimed to assess the prevalence of abnormal serum cholinesterase among 183 vegetable growers in a district in Ubon Ratchathani Province. Blood samples were collected from two groups of participants using the accidental sampling method: farmers applying pesticides on their farm and farmers growing organic vegetables. Data were analyzed using frequency counts and percentages. The results showed that 51.18% of the vegetable farmers using pesticides on their farm had unsafe serum cholinesterase levels and 48.03% of them were at risk. As for the organic vegetable growers, 33.93% of them had unsafe serum cholinesterase levels and were at risk. Therefore, the concerned agencies should educate the farmers and promote organic farming as an alternative to pesticide use in their vegetable production to minimize the effects of pesticides on human health and the environment.